Impact of the 2017 tax cuts and jobs act on labor supply and welfare of married households - Julie L. Hotchkiss; Robert E. Moore; Fernando Rios-Avila (Federal Reserve Bank of Atlanta, 2021)
This paper calculates the change in optimal labor supply and total family welfare resulting from the Tax Cuts and Jobs Act of 2017 (TCJA). We estimate labor supply elasticities for married families in the Current Population Survey from 2015 to 2017, using a joint family utility model. These elasticities are then used to simulate changes in optimal labor supply and resulting change in welfare among families with different characteristics under the new TCJA tax code. We find that optimal hours are lower post-TCJA, relative to before. However, there are differences across family members and family types. Both men's and women's optimal hours decline with income starting in the second quintile, but the decline is more dramatic for men. Overall, all families' welfare increased post-TCJA, with the gains in welfare disproportionately benefiting the wealthy; families with any self-employment income; families with children; and families renting, versus owning, their home.
Keywords: I30; J22; D19; 330; family welfare; joint labor supply; microsimulation; TCJA